2016
DOI: 10.2500/ar.2016.7.0157
|View full text |Cite
|
Sign up to set email alerts
|

Are Respiratory Viruses Involved in Preseasonal Symptoms or Severity in Japanese Cedar Pollinosis?

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…By contrast, our studies of the potential involvement of respiratory viral infections in preseasonal symptoms did not establish a correlation. 25 Our results with bacterial cultures indicated that neutrophilia occurred in a greater proportion of PreSyP than in PreAsP subjects. Moreover, nasal carriage of S. aureus in PreAsP and PreSyP was 79% and 75%, Figure 2.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…By contrast, our studies of the potential involvement of respiratory viral infections in preseasonal symptoms did not establish a correlation. 25 Our results with bacterial cultures indicated that neutrophilia occurred in a greater proportion of PreSyP than in PreAsP subjects. Moreover, nasal carriage of S. aureus in PreAsP and PreSyP was 79% and 75%, Figure 2.…”
Section: Discussionmentioning
confidence: 53%
“…By contrast, our studies of the potential involvement of respiratory viral infections in preseasonal symptoms did not establish a correlation. 25…”
Section: Discussionmentioning
confidence: 99%